2017
DOI: 10.1007/s00792-017-0957-8
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of protein oxidation correlates with the desiccation and radiation resistance of hot and cold desert strains of the cyanobacterium Chroococcidiopsis

Abstract: To investigate the relationship between desiccation and the extent of protein oxidation in desert strains of Chroococcidiopsis a selection of 10 isolates from hot and cold deserts and the terrestrial cyanobacterium Chroococcidiopsis thermalis sp. PCC 7203 were exposed to desiccation (air-drying) and analyzed for survival. Strain CCMEE 029 from the Negev desert and the aquatic cyanobacterium Synechocystis sp. PCC 6803 were further investigated for protein oxidation after desiccation (drying over silica gel), tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 36 publications
2
55
0
Order By: Relevance
“…However, strains with high resistance (up to 15%) to sodium chloride were found. It was previously shown that the same physiological mechanism provides resistance for both desiccation and salinization, which could explains the obtained result [77,78].…”
Section: Discussionsupporting
confidence: 62%
“…However, strains with high resistance (up to 15%) to sodium chloride were found. It was previously shown that the same physiological mechanism provides resistance for both desiccation and salinization, which could explains the obtained result [77,78].…”
Section: Discussionsupporting
confidence: 62%
“…The correlation between radiation and desiccation tolerance is also seen in the gram negative pathogenic bacterium, Acinetobacter radioresistans, which can reportedly tolerate gamma radiation as high as 25 kGy and desiccation stress as long as 157 days at 31% relative humidity [119]. Recently, a tight correlation is reported between desiccation, radiation tolerance, and avoidance of protein oxidation in desert strains of Chrococcidiopsis, where the protein oxidation damage was low when long term desiccated cells were exposed to H 2 O 2 or gamma radiation stress [161]. The radioresistance of these microbes may therefore to be incidental, that is, a consequence of acquired desiccation tolerance.…”
Section: Radiation and Desiccation Stress Responsementioning
confidence: 99%
“…In nature they occur in extremely hot and cold deserts, considered the closest analogs of Mars , there forming hypolithic or endolithic biofilms at the soil-rock interface or inside porous rocks (Friedmann and Ocampo, 1976;Friedmann, 1980;Grilli Caiola and Billi, 2007). Under laboratory conditions, these desert cyanobacteria survive years of airdrying (Billi, 2009;Fagliarone et al, 2017) and, when irradiated in the dried state, can tolerate up to 24 kGy of gamma rays and 30 kJ/m 2 of Marslike UV flux (Cockell et al, 2005). These features make desert strains of Chroococcidiopsis ideal candidates for investigating life endurance under space and Mars-like conditions in LEO by using the ESA EXPOSE facility, a platform that allows passive exposure to space conditions of dried samples subsequently analyzed after retrieval back on Earth .…”
Section: Introductionmentioning
confidence: 99%